Intervention design elements are associated with frontline health workers’ performance to deliver infant and young child nutrition services in Bangladesh and Vietnam - Nguyen, Phuong Hong; Kim, Sunny S.; Tran, Lan Mai; Menon, Purnima; Frongillo, Edward A. (Elsevier, 2019)
Frontline health workers (FLWs) are needed for delivering interventions at scale to reduce maternal and child undernutrition, but low- and middle-income countries often face inadequate FLW performance.